Congenital Rhabdomyosarcoma Presenting as a Neck Mass at Birth. (30th July 2018) - Waldman, Leah E.; Williamson, Alex K.; Amodio, John B.; Collins, Lee
Abstract : Rhabdomyosarcoma is a malignant tumor of the soft tissues which preferentially affects the pediatric population. Neonatal rhabdomyosarcoma is rare, and much of the published literature concerning this entity consists of isolated case reports and small case series. Recent work involving the classification of rhabdomyosarcoma has helped to delineate prognostic information based on gene rearrangements. Here, we present a case of congenital rhabdomyosarcoma seen in utero which manifested as a neck mass at birth and was found to harbor a favorable gene fusion.